Pengaruh Bahasa Gaul (SLANG) Terhadap Bahasa Indonesia Pada Generasi Muda - Nurasiah Anggini; Nabila Yun Afifah; Edi Syaputra (Universitas Dehasen Bengkulu, 2022)
This research was developed based on the problems that exist in adolescents. This study aims to develop and find out the language used by today's youth. Language is the hallmark of a country as a means of communication. Everyone must need language in interacting with fellow human beings, expressing ideas and even opinions and other social discussion relationships. With the development of the era, the language spoken by teenagers today is slang. Slang is not only used by teenagers, even parents also use it both in writing and verbally, formally and informally. This results in the use of language being not good and correct. We should be able to use Indonesian properly and correctly, therefore Indonesian remains the national language and is maintained. Slang is the typical language of teenagers